2020
DOI: 10.1016/j.biopsych.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Exposure via Lactation in Rats Disrupts Perinatal Programming of the Gamma-Aminobutyric Acid Trajectory and Select Early-Life Behaviors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 97 publications
(123 reference statements)
3
44
0
Order By: Relevance
“…In rodent models, exposure to cannabinoids (both synthetic and plant-derived) during gestation or early development induces an array of deleterious consequences on behavior manifesting both at early life and adulthood 20,[26][27][28]34,35 . Previously, we have shown that the administration of cannabinoids to lactating dams during the early postnatal period causes significant delays in both synaptic and behavioral development 28 . Here, we used the same protocol of perinatal cannabinoid exposure in order to determine if such early-life exposure results in consequences lasting into adulthood.…”
Section: Perinatal Thc Exposure Augments Social Exploration At the Comentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent models, exposure to cannabinoids (both synthetic and plant-derived) during gestation or early development induces an array of deleterious consequences on behavior manifesting both at early life and adulthood 20,[26][27][28]34,35 . Previously, we have shown that the administration of cannabinoids to lactating dams during the early postnatal period causes significant delays in both synaptic and behavioral development 28 . Here, we used the same protocol of perinatal cannabinoid exposure in order to determine if such early-life exposure results in consequences lasting into adulthood.…”
Section: Perinatal Thc Exposure Augments Social Exploration At the Comentioning
confidence: 99%
“…During the early postnatal period, we have shown that exposure to exogenous cannabinoids via lactation also alters the developmental trajectory of the PFC 28 . Specifically, the timeline of cell excitability changes mediated by GABAergic maturation is delayed by exposure to either THC or a synthetic agonist of CB1R.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that exposure to cannabinoids via lactation alters the developmental trajectory of the prefrontal cortex (PFC), which has been identified as a cortical hub essential to planning, cognitive flexibility and emotional behaviors (Goldman-Rakic, 1990) and a common target in various endocannabinoid-related synaptopathies (Araque et al, 2017). Our work revealed that exposure of lactating females to either THC, or a synthetic agonist of CB1R, altered the maturational trajectory of GABAergic transmission and led to behavioral abnormalities in early life (Scheyer et al, 2020b). Very recently, we reported that perinatal THC exposure via lactation elicited lasting, deleterious impacts on social behavior and synaptic plasticity in the PFC of the adult offspring (Scheyer et al, 2020a).…”
Section: Introductionmentioning
confidence: 80%
“…Cannabis consumption by pregnant women is progressively increasing 1-4. The principle psychoactive component of cannabis, ∆ 9-tetrahydrocannabinol (THC), in addition to other cannabinoids, is actively transferred to the developing infant via breastfeeding (Hurd et al, 2019;Scheyer et al, 2019Scheyer et al, , 2020aScheyer et al, , 2020b. During the perinatal period (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation